Genome‐wide identification of the traf gene family in yellow catfish (Pelteobagrus fulvidraco) and analysis of their expression in response to bacterial challenge. Issue 3 (22nd June 2022) - Nie, Zhiwei; Wang, Bo; Zhang, Zhixuan; Jia, Zeming; Xu, Runjie; Wang, Heyu; Zhou, Wei; Gong, Yifu
Abstract: Tumour necrosis factor (TNF) receptor‐associated factor (TRAF) is a receptor protein that has important functions in the immune system. Nonetheless, there have been few reports of traf genes in teleost fishes. The present study aimed to identify the traf genes from the genomic information of yellow catfish ( Pelteobagrus fulvidraco ). Eight traf genes were identified and named, which are distributed on different chromosomes but have similar conserved protein domains. Phylogenetic and syntenic analyses demonstrated conservation of traf genes during evolution. In addition, yellow catfish has the relatively rare traf1 and traf5 genes. Gene structure and motif analysis revealed the homology and distribution diversity of the traf genes. Quantitative real‐time reverse transcription PCR was used to study the expression patterns of traf genes in healthy fish tissues and after infection by Aeromonas hydrophila . The results demonstrated significant changes in traf gene expression, indicating a potential role in innate immunity.